Enhancing Innovative Work Behaviour Through Job Autonomy: The Role Of Intrinsic Work Motivation Among Primary School Teachers In North Bengkulu - DEWI, FELISHA KUSUMA; Pareke, Fahrudin Js (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze how elementary school teachers can improve innovative work behavior (IWB) with job autonomy (JA) and the role of intrinsic motivation (IM) among them. using a quantitative approach with a population of 882 elementary school teachers in North Bengkulu. While the research sample was determined using a purposive sampling technique by considering the criteria of teachers who are actively teaching. The number of respondents who participated was 260 teachers. Data were collected using a validated questionnaire that measures work autonomy, intrinsic motivation, and innovative work behavior. Validity and reliability were tested through factor loading, Cronbach's Alpha, Composite Reliability (CR), and Average Variance Extracted (AVE). Data were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS) through SmartPLS 4. The research findings indicate that job autonomy has a significant positive effect on intrinsic motivation and innovative work behavior. Intrinsic motivation also has a positive effect on innovative work behavior; however, its mediating role between job autonomy and innovative behavior is not statistically significant. This suggests that autonomy directly drives teachers' innovative behavior, while intrinsic motivation strengthens their engagement but does not fully explain the relationship. This study was only conducted on elementary school teachers in North Bengkulu, so the results cannot be generalized. This study is expected to provide further information and understanding regarding the role of intrinsic motivation as a mediator and the influence of job autonomy in improving teachers' innovative work behavior, in order to help students better understand learning in a more innovative way.